Observation of the Quantum-Confined Stark Effect in a GaAs/AlGaAs P-I-N Diode by Room Temperature Photocurrent Spectroscopy - Ison, C. S.; Estacio, E. S.; Bailon, M. F.; Salvador, A. A. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Room temperature photocurrent spectroscopy is performed on an MBE-grown GaAs/AlGaAs MQW p-i-n device. An observed shift to longer wavelengths is seen with increasing reverse bias voltages. This behavior is explained through a mechanism called the Quantum-Confined Stark Effect. Applied electric fields are estimated using second-order correction for infinite quantum wells. The estimated built-in electric field is 20 kV/cm corresponding to a 9-meV shift from the flatband energy transition. An observed shift to shorter wavelengths is seen under an optically applied field for both biased and unbiased conditions.